The creation of educational resources through the use of blogs during the lockdown period: A case study of a nursery school - Ruiz-Bejarano, Aurora María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
During the early stages of the Covid-19 pandemic, educational centres made a considerable effort to adapt to the unforeseen circumstances. This article analyses how a nursery school (0-3 years) used a blog between the months of March and June 2020. It examines the use of a blog to develop and implement educational materials and activities that were targeted at the school’s students and families who were confined at home. The use of a blog allowed the educational staff to maintain the same educational approach that the nursery school had been using since its beginnings.